Mycetophilous beetles (Coleoptera) of the Saratov Oblast: The results of fi ve years of research - Sazhnev, Alexey Sergeevich; Ashcheulova, Anastasiya A. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
During fi ve years of research (2017–2020 and 2022), 257 fruiting bodies of 34 species of basidiomycetes from the orders Agaricales and Polyporales, Hymenochaetales, Boletaceae, Russulales and Gloeophyllales were collected in diff erent areas of the Saratov region. 108 species of Coleoptera from 24 families were identifi ed that are directly and/or indirectly associated with the fruiting bodies of fungi. The highest species diversity was noted in the families Staphylinidae – 37 species, Tenebrionidae – 11, Ciidae – 10, Erotylidae and Mycetophagidae – 6 species each. In terms of frequency of occurrence, Diaperis boleti predominates, found on 16 (out of 34) basidiomycetes, Dacne bipustulata (13), Mycetophagus quadripustulatus (12) and Gyrophaena joyi (11). The same mycetobiont species dominate in the collections in terms of abundance of Diaperis boleti (30.6%), Dacne bipustulata (17.7%), Mycetophagus quadripustulatus (10.2%) and Gyrophaena joyi (7.9%). For four fungal species (with perennial and annual cycles of fruiting body development), the succession of mycetophilous Coleoptera could be traced. The trophic groups of Coleoptera on fungi are mainly represented by mycetophages in the broad sense (72.5%), predators (14.1%), sapronecrophages and detritivores (13.4%).